Health dialogue intervention versus opportunistic screening in primary care for type 2 diabetes and cardiovascular disease prevention in settings with low socioeconomic status (DETECT): study protocol for a pragmatic cluster-randomized trial - Ballin, Marcel; Backman Enelius, Moa; Dini, Samira; Galanti, Maria Rosaria; Hagströmer, Maria; Heintz, Emelie; Lager, Anton; de Leon, Antonio Ponce; Lundh, Lena; Nystrand, Camilla; Walldin, Christina; Augustsson, Hanna (Current controlled trials in cardiovascular medicine, 2024)
Background Meta-analyses of randomized trials suggest that health checks and health promotion interventions targeting behavior change in primary care do not prevent cardiovascular morbidity and mortality in the general population. However, whether such interventions are more effective in high-risk populations, such as people living in low socioeconomic settings, remains unclear, as they have been poorly represented in previous trials. Therefore, we aim to evaluate the effectiveness, cost-effectiveness, and implementation of systematic screening followed by an individually oriented, lifestyle-focused, health dialogue intervention for prevention of type 2 diabetes and cardiovascular disease, as compared to opportunistic screening, in primary care in socioeconomically disadvantaged areas. Methods Using an overall pragmatic approach and a cluster-randomized design with two arms, we aim to enroll 3000 participants aged 50–59 years from 30 primary care centers (PCCs) with an above-average level of Care Need Index in Stockholm Region, Sweden. PCCs will be randomized (1:1) either to a health dialogue intervention, which includes inviting enlisted patients to a systematic screening of risk factors followed by an individually oriented lifestyle-focused health dialogue, or to opportunistic screening, which includes screening patients for a smaller set of risk factors during an appointment at their PCC taking place for other reasons. The main outcome will be change in systolic blood pressure during 6- and 12-month follow-ups. Additional short-term outcomes will be changes in other biological risk factors, health-related quality-of-life, and lifestyle habits, as well as process and implementation outcomes, and unintended side effects. The long-term effect on type 2 diabetes and cardiovascular disease incidence and mortality will be examined using regional and nationwide registers. Changes in systolic blood pressure and other health outcomes will be analyzed using mixed-effect generalized linear modeling and mixed-effect Cox regression to capture variability between and within PCCs. A health economic evaluation will assess resource use and costs in the short- and long-term. Discussion This trial of lifestyle-focused health dialogues and opportunistic screening in primary care in socioeconomically disadvantaged areas in the largest region of Sweden has the potential to yield valuable insights that could support evidence-based policymaking. Trial registration ClinicalTrials.gov (NCT06067178). Prospectively registered September 27, 2023.